Effect of mechanical insufflation‐exsufflation in children with neuromuscular weakness - Veldhoen, Esther S. (Pediatr Pulmonol, 2020)
INTRODUCTION: Children with neuromuscular diseases develop cough impairment. Airway clearance techniques (ACTs) may help to prevent recurrent respiratory tract infections (RTIs). A commonly used ACT is mechanical insufflation‐exsufflation (MI‐E), but evidence for efficacy is limited. We hypothesize that MI‐E has beneficial effect on RTI related hospital admission rate. METHODS: In this single‐center retrospective study, we reviewed all children who used daily MI‐E between 2005 till June 2019. Primary outcome studied was the number of RTIs requiring hospital admission. Patient satisfaction and burden experienced by MI‐E use were explored by questionnaires using a Likert scale. The relative number of RTIs requiring admission and the number of admission days per eligible period before and after the introduction of MI‐E were compared using the Friedman test and the Wilcoxon signed‐rank test. RESULTS: Thirty‐seven children were included. The median number of RTI related hospital admissions per 1000 eligible days after the introduction of MI‐E was 0.9 (interquartile range [IQR] 0.0‐3.1) compared to the 3 preceding years (median 3.7; IQR 1.4‐5.9; P = .006). The median number of RTI related admission days per 1000 eligible days after the introduction of MI‐E was significantly lower with a median of 2.7 (IQR 0.0‐17.4) compared to the 3 preceding years (median 33.6; IQR 15.0‐51.1; P = .001). Patient satisfaction was high with low burden, even in patients who discontinued treatment. CONCLUSION: A significantly lower number of RTIs requiring hospital admission and shorter admission duration after the introduction of MI‐E was found, with high patient satisfaction and low burden.